Changes in body core temperature during the cycling segment of a triathlon - Riska, D.; Putala, M.; Grznar, L.; Tolkounov, T. (Journal of Physical Education and Sport, 2024)
This study investigates how body core temperature varies during the cycling segment of a triathlon under different outdoor temperatures. Because high external temperatures can mimic some effects of altitude training, we examined the impact of varying external temperatures on body core temperature, heart rate levels, blood lactate values, and perceived exertion. The research involved Slovak triathletes, aged 23(±2) years, who regularly compete in European Cup races. Probands completed 2 rides at the anaerobic lactate threshold level in two different outdoor temperatures, namely 18 °C and 30 °C on bicycle trainers. We assumed significant changes in all monitored parameters at a higher outdoor temperature and we assumed a significant relationship between the outdoor temperature and the monitored parameters. We found a significantly higher level of heart rate during riding at a higher temperature (p < 0.01**). We measured the subjective level of load using the Borg scale, and we also found a significantly higher level (p < 0.05*). The relationship between body core temperature and the subjective feeling of load came out at the level of r =0.8056; r²= 0,6489; p < 0.01** when riding in low temperature and r =0.6998; r²= 0,4897; p<0.05* when riding in high outside temperature. The relationship between core body temperature and blood lactate level was r=0.695; r² = 0,4830; p < 0.05* when riding in low temperature and r =0.7356; r²=0,5411; p<0.05* when riding in high temperature. In view of these findings, we recommend that when training in high temperatures, you monitor the parameters during the training in detail and pay attention to the exact execution of the training.